A Case Study: Application of Music Therapy in Chronic Obstructive Pulmonary Disease (COPD) Patients at RSUD Tarakan Jakarta - Jaemi; Yani Sofiani; Ninik Yuniatri; Wariani, Wiwik (Alta Dharma Publisher, 2022)
Background: Anxiety is a typical complaint experienced by COPD patients. Pharmacological therapy is one of the primary interventions used to reduce anxiety. However, this therapy is not optimal and ultimately reduces anxiety. Therefore, additional treatment is needed. Objective: This study aims to measure the effect of music therapy in reducing anxiety in COPD patients. Method: A case study was applied among 15 COPD patients. HADS was used to assess anxiety. Paired t-test was used as a statistical test. Result: This case study resulted that nursing care being prepared based on Indonesian nursing standards consisting of the SDKI, the SIKI, and the SLKI. Then the application of music therapy effectively reduced anxiety with a p-value of 0.000 (p< 0.05). Conclusion: It can be concluded that music therapy could reduce anxiety in these fifteen patients. Recommendation for the clinical practice: it is recommended that nurses can apply this intervention to improve the quality of nursing care plans